Unveiling the outer core composition with neutrino oscillation tomography - Maderer, Lukas; Kaminski, Edouard; Coelho, João A. B.; Bourret, Simon; Van Elewyck, Véronique (Frontiers in Earth Science, 2023)
In the last 70 years, geophysics has established that the Earth’s outer core is a Fe-Ni alloy containing a few percent of light elements, whose nature and amount remain controversial today. Besides the classical combinations of silicon and oxygen, hydrogen has been advocated as the only light element that could account alone for the density and velocity profiles of the outer core. Here we show how this question can be addressed from an independent viewpoint, by exploiting the tomographic information provided by atmospheric neutrinos, weakly-interacting particles produced in the atmosphere and constantly traversing the Earth. We evaluate the potential of the upcoming generation of atmospheric neutrino detectors for such a measurement, showing that they could efficiently detect the presence of 1 wt% hydrogen in a FeNi core in 50 years of concomitant data taking. We then identify the main requirements for a next-generation detector to perform this measurement in a few years timescale, with the further capability to efficiently discriminate between FeNiH and FeNiSi(x)O(y) models in less than 15 years.